Enhanced mechanical properties are possible with urethane dimethacrylate-based experimental restorative dental composite. (16th October 2020) - Khan, Aftab Ahmed; AlKhureif, Abdulaziz Abdullah; Mohamed, Badreldin A; Bautista, Leonel S J
Abstract: This laboratory study aimed to replace the traditional bisphenol A-glycidyl methacrylate ( bis GMA) resin system with a urethane dimethacrylate (UDMA)-based resin system to enhance the physicomechanical properties of dental restorative composite (DRC). We evaluated surface roughness, porosity %, nanohardness, elastic modulus, and compressive strength (CS) in the control group (the bis GMA-resin system) and two experimental groups (UDMA-based resin systems with 20 wt.% SiO2 or Al2 O3, each 30 μ m in size spherical fillers). Cylindrically shaped samples 4 mm in diameter and 6 mm in height were fabricated using light curing (n = 10). One-way analysis of variance method was used to statistically analyze the results (p ≤ 0.05). The data suggest that both UDMA-based resin systems showed increased surface roughness (Ra ) and porosity % in the sample fabrication compared with the control. However, the nanohardness in both SiO2 -based UDMA composite (0.20 ± 0.09 GPa) and Al2 O3 -based UDMA composite (0.22 ± 0.07 GPa) was not significantly higher compared with the control (0.19 ± 0.05 GPa). Likewise, while improved CS values were observed in both SiO2 -based UDMA composite (15.5 ± 1.9 MPa) and Al2 O3 -based UDMA composite (16.2 ± 0.7 MPa) compared to the control (14.5 ± 4.5 MPa), this increase was not statistically significant. The newly developed UDMA-based resin formulation with Al2 O3 micro-filler showed promising physicomechanical properties and may be appropriate for use as DRC.